Luqman al-Hakim dan keledai / Idris Sadri & Rendra M. Ridwan ; editor Rony Amdani ; ilustrator Rendra M. Ridwan. - IDRIS SADRI; Rendra M. Ridwan; Rony Amdani (Mizan Pustaka, 2015)
20 hlm. : ilus. ; 18 cm [3 eks.]